The limits of growth of the multidivisional firm: A case study of the U.S. oil industry from 1930‐90 - Öllinger, Michael (Strategic Management Journal, 1994)
Abstract Some scholars (Chandler, 1977; Penrose, 1959) believe that firms grow by transferring inimitable marketing, production, and research skills from one line of business to another. Extending this view and emphasizing the role of the central office of a multidivisional firm to transfer administrative skills, Williamson (1975) argues that competition among business units within the firm mimics a competitive capital market and leads to an effcient allocation of resources. Coase (1937), however, argues that firm size is limited by the costs of organizing diverse transactions and Chandler (1991) claims that growth is constrained by the technical and marketing expertise of the top managers. The purpose of this paper is to demonstrate that the scope of the multidivisional firm is limited by the transferability of firm‐specific skills and the efficiency of capital markets. Support comes from a case study of 19 oil companies over the 1930–90 period.